Four raised to one equals one: A genetic approach to the Pseudolaelia vellozicola complex does not follow a math rule - Nazareno, Alison Gonçalves; Neto, Luiz Menini; Buzatti, Renata Santiago de Oliveira; Berg, Cássio van den; Forzza, Rafaela Campostrini (Ecology and evolution, 2020)
Pseudolaelia is a genus endemic to the eastern Brazilian Atlantic Forest, consisting of 12 accepted species. Some Pseudolaelia species, such as P. vellozicola, P. aguadocensis, P. oliveirana, and P. regentii, referred to here as the PV complex, present extensive intra‐ and interpopulation morphological polymorphism, raising uncertainty regarding their circumscriptions. Although previous morphological analyses were used to solve the generic boundaries in the PV complex, persuasive genetic evidence is lacking. In order to test the hypothesis that the group under investigation contains only one taxon, amplification profiles of five intersimple sequence repeat (ISSR) markers were used to evaluate genetic diversity, genetic structure, and the relationships among the PV complex species. A total of 134 reproductive individuals were sampled in eight insular populations. Intrapopulation genetic analysis indicated low levels of genetic diversity. Analysis of genetic structure revealed that each of the eight sample locations can be considered unique biological populations as they are highly differentiated from each other. The Mantel test showed a high and positive correlation between genetic and geographic distance (r = .841, p < .002), indicating isolation by distance. The results are consistent with that expected for plants with insular geographical distribution. When testing for the null hypothesis, the low levels of genetic variation among species (FCT = 0.155) suggest that the populations constitute only one highly polymorphic species with a wide distribution. Analysis of genetic structure revealed that each of the eight sample localities can be considered unique biological populations as they are highly differentiated from each other. The results are consistent with that expected for plants with insular geographical distribution. When testing for the null hypothesis, the low levels of genetic variation among species suggest that the populations constitute only one highly polymorphic species with a wide distribution.